Nation [compact disc, unabridged] - Pratchett, Terry (Harper Children's Audio, 2008)
A vicious storm has ripped away everything that Mau knows, and he now stands as the lone inhabitant of a desert island. However, when her ship flounders, Daphne joins Mau on the island, and the two work towards surviving together. The lessons that follow create a deep bond of understanding between Mau and Daphne, as they synchronously form their own Nation.